Factors Affecting Holistic Development of Preschoolers in Islamabad, Pakistan - Yunus, Saima; Khan, Fahad Munir; Khan, Abdul Ahad Munir; Khan, Maaz Munir; Khan, Abdur Rafay Munir (2025)
This study explores the factors that affect young children's overall development—such as thinking, speaking, and social skills—in a village near Islamabad, Pakistan. It highlights the importance of early childhood education in shaping a child’s future. The research focused on whether children had any learning experience before preschool, how much parents know about education, the role of the community and politics, and how well school lessons support a child’s full growth. To gather information, the researcher used forms, interviews, and classroom observations with 25 participants, including parents, teachers, and school leaders. The study also looked at parental involvement, teacher training, cultural influences, and efforts by the Pakistani government and organizations like UNICEF to improve early education Early Childhood Education (ECE) supports children’s growth from birth to age 8 in areas like thinking, emotions, movement, language, and social skills. It plays a vital role in preparing children for school and life. While Pakistan’s National Education Policy (2009) recognizes the value of ECE, rural areas near Islamabad still face major challenges such as untrained teachers, poor facilities, and cultural barriers.